Islamic Prayer Time Calculation in High-Latitude Summer: A Computational Approach Using the Ittibāʿ Aqrab al-Bilād Method in Iceland - Mayrisa Andriyani; Siti Nurwilda; Sofiyah Sofiyah; A’isyah Wulandari; Wahyu Ningtiyas Mergianti; Nurissaidah Ulinnuha (Fakultas Syari'ah dan Hukum UIN Walisongo, 2026)
Determining Islamic prayer times in high-latitude regions is challenging, particularly during summer when continuous twilight prevents the Sun from reaching required depression angles below the horizon. This condition causes conventional solar-angle-based methods to produce undefined (NaN) values for Fajr and Isha. This study proposes a computational approach to address this limitation using Reykjavik, Iceland, as a case study. Astronomical calculations based on solar position parameters are applied to determine Dhuhr, Asr, and Maghrib. At the same time, the ittibā’ aqrab al-bilād method is used to resolve Fajr and Isha by referencing London as the nearest region with normal day–night cycles. The method is implemented in a GUI-based prayer time calculator. Validation shows that the computed times have acceptable deviations, averaging 14–15 minutes compared to established applications, with larger discrepancies for Isha due to persistent twilight. This study offers a practical, computational, and jurisprudential solution to determining prayer times in extreme latitudes.